2021
DOI: 10.1007/s00520-021-06310-w
|View full text |Cite
|
Sign up to set email alerts
|

A Japanese translation, cultural adaptation, and linguistic and content validity confirmation of the Scored Patient-Generated Subjective Global Assessment

Abstract: Purpose The Scored Patient-Generated Subjective Global Assessment (PG-SGA © ) is a globally recognized and used nutritional screening, assessment, monitoring, and triaging tool. The aim of this study was to translate and culturally adapt the original English PG-SGA for the Japanese speaking populations and to assess its linguistic validity (i.e., comprehensibility, difficulty) and content validity, as perceived by Japanese patients and healthcare professionals. Methods In accordance with methodology used in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…Comprehensibility and di culty of the professional component of the Polish version of the PG-SGA were considered acceptable by HCPs (S-CI = 0.87 and S-DI = 0.80, respectively). These results are in contrast to the results of the Norwegian [24], German [20], Dutch [19], Japanese [22] and Thai [26] studies, in which the professional component of the PG-SGA scored below acceptance in the constructs of di culty, and additionally of comprehensibility in the Norwegian study [24]. On the other hand, in a recently published study on the validation of the Greek version of the PG-SGA [21], comprehensibility and di culty of the professional component were perceived as excellent (≥ 0.90).…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Comprehensibility and di culty of the professional component of the Polish version of the PG-SGA were considered acceptable by HCPs (S-CI = 0.87 and S-DI = 0.80, respectively). These results are in contrast to the results of the Norwegian [24], German [20], Dutch [19], Japanese [22] and Thai [26] studies, in which the professional component of the PG-SGA scored below acceptance in the constructs of di culty, and additionally of comprehensibility in the Norwegian study [24]. On the other hand, in a recently published study on the validation of the Greek version of the PG-SGA [21], comprehensibility and di culty of the professional component were perceived as excellent (≥ 0.90).…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, HCPs indicated that the patient component of the Polish version of the PGSGA was relevant. Similar results on the patient component were obtained in other studies performed in Denmark [19], Germany [20], Norway [24], Greece [21], Japan [22], the Netherlands [25], Thailand [26] and Italy [27]. In all mentioned studies, content validity, as well as comprehensibility and di culty of the PG-SGA Short Form were perceived as excellent.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations